Alopecia areata - Papadopoulos, A... J. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2000)
Alopecia areata is a common, unpredictable, non-scarring form of hair loss. This disorder affects all age groups, with a higher prevalence in children andadolescents. Limited scalp involvement is the most common presentation but more severe forms of the disorder, involving the entire scalp or body, also exist. Research has linked alopecia areata with certain HLA-Class II alleles, implicating an autoimmune etiology. Various therapeutic modalities have been employed to gain clinically acceptable hair regrowth.
Keywords: Alopecia areata; alopecija; Anthralin; Cyclosporine; Diagnosis; Diagnosis, differential; Etiology; Glucocorticoids; kožne bolezni; lasišče; Minoxidil; Puva therapy; Therapy; zdravljenje